Antibacterial Susceptibility Patterns of Common Bacterial Species Associated with Urinary Tract Infections in Patients Attending Kam Medical and Diagnostic Centre, Kampala Uganda. - Turyatunga, Gerald; Wito, Sarah Gift; Muwagunzi, Enoch (Student’s Journal of Health Research Africa, 2021)
Background: Urinary tract infection (UTI) is defined as the presence of microbial pathogens within the urinary tract. It is primarily caused by Escherichia coli (E.coli), accounting for 75% of all bacterial UTI cases. Bacteria such Klebsiella pneumonia, Proteus mirabilis, Staphylococcus aureus, Pseudomonas aeruginosa, and Enterococcus faecalis have also been reported as causative agents. The study aimed to determine the antibiotic susceptibility patterns of Uropathogenic bacteria in urine samples of patients with suspected UTI in Kam Medical and the diagnostic Centre. Methodology: This was a cross-sectional study where 120 urinary samples from Kam Medical and Diagnostic Centre in 2019. The urine specimens were cultured on CLED (Cysteine Lactose Electrolyte – Deficient) and blood agar media. Kirby-Bauer’s standard disk diffusion method was applied to test the susceptibility of the drug for Mueller-Hinton culture agar plates. Results: All 120 patients suspected of UTI had bacterial pathogen causing UTI. Among the urinary pathogens, Escherichia coli was the most common in 85/120 (70.8%) of the patients followed by S.aureus 13/120 (10.8 %), Klebsiella spp 4/120 (9.2%), Enterococcus spp with 4/120 3.3 %), Pseudomonas aeruginosa with 4/120 (3.3%) and Proteus with 3/120 (2.5%). According to the results of the antibiogram, the highest resistance was observed for Nalidixic acid (64.2%), Ampicillin (61.7%), and Cotrimoxazole (54.2 %). The highest susceptibility (antibiotic sensitivity) was observed with imipenem (97.5%), Nitrofurantoin (49.2 %), Ciprofloxacin (45.8%), and Clotrimazole (44.2 %) Conclusion and recommendations: The bacterial pathogens associated with UTIs in this study were E.coli species, Staphylococcus aureus, Klebsiella, Enterococcus species, Pseudomonas species, and Proteus species. E.coli was the most common isolate followed by S.aureus, Klebsiella spp, Pseudomonas spp, and Enterococcus spp, and lastly Proteus spp. The highest levels of bacterial resistance were recorded against first-generation antibiotic drugs. Bacterial isolates in this study were highly susceptible to broad-spectrum, second/ third generation antibiotics drugs.